2016
DOI: 10.18632/oncotarget.7259
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide inhibits glioma cell growth through induction of telomerase displacement and telomere dysfunction

Abstract: Glioblastomas are resistant to many kinds of treatment, including chemotherapy, radiation and other adjuvant therapies. As2O3 reportedly induces ROS generation in cells, suggesting it may be able to induce telomerase suppression and telomere dysfunction in glioblastoma cells. We show here that As2O3 induces ROS generation as well as telomerase phosphorylation in U87, U251, SHG4 and C6 glioma cells. It also induces translocation of telomerase from the nucleus to the cytoplasm, thereby decreasing total telomeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…Immunofluorescence was performed as previously reported [17]. Cells were fixed in 2% formaldehyde and permeabilized in 0.25% Triton X100 in phosphate buffered saline (PBS) for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence was performed as previously reported [17]. Cells were fixed in 2% formaldehyde and permeabilized in 0.25% Triton X100 in phosphate buffered saline (PBS) for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[30][31][32] It has been also reported that As 2 O 3 treatment leads to damage to telomeres. 33 We then studied whether Mus81 sumoylation was involved in DNA damage responses after exposure to metal toxins including arsenic and chromium . Consistent with an early report, 33 ATO exposure triggered DNA damage responses manifested as elevated levels of phosphorylated H2AX (g-H2AX) and phosphorylated ATM (p-ATM); however, cells expressing transfected His 6 -Mus81-5R plasmid displayed a reduced level of g-H2AX compared with cells transfected with the WT counterpart (Fig.…”
Section: Compromised Dna Damage Response In Cells Expressing Mus81-5rmentioning
confidence: 99%
“…9,10 Interestingly, some studies have shown that ATO could also inhibit growth and induce apoptosis in a variety of solid tumor cells, such as breast, liver, gastric, prostate, renal, bladder, and glioma cells. [10][11][12][13][14] However, several limitations hinder its applications in clinical practice. The free ATO in aqueous solution exists as arsenite ions, with fast elimination in vivo, poor pharmacokinetics, and unacceptable systemic toxicity, including peripheral neuropathies and liver failure.…”
Section: Introductionmentioning
confidence: 99%